THE EFFECTIVENESS OF AUGMENTED REALITY TECHNOLOGY ON THE MOTIVATION TO LEARN ISLAMIC RELIGIOUS EDUCATION IN VOCATIONAL SCHOOLS - Fitria N.S Rahmadana; Suparto Iribaram; Abdul Azis Khoiri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Islamic Religious Education (IRE) learning in secondary schools is still often conducted using conventional methods, resulting in suboptimal student participation and learning motivation. The development of educational technology provides opportunities to create more interactive learning experiences, one of which is through the use of Augmented Reality (AR) technology. This study aims to analyze the effectiveness of AR-based learning in improving students learning motivation in PAI subjects at Vocational High School (SMK). This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design and purposive sampling technique. The research subject cosisted of 46 students divided into an experimental group (n = 21) and a control group (n = 25). Learning motivation was measured using a questionnaire based on the ARCS model (Attention, Relevance, Confidence, and Satifaction). Data analysis was conducted using descriptive statistics (Mean and N-Gain), and inferential statistics, including prerequisite tests, paired sample t-test, independent sample t-test, complemented by effect size analysis using cohen’s d. The result indicated a significant difference in learning motivation between the experimental and control groups after treatment (p < 0.0001) with a cohen’s d value of 1.767, indicating a large effect size. These findings suggest that AR-based learning is effective in enhancing students learning motivation in Islamic Religious Education.